Sexual dimorphic response to rituximab treatment: A longitudinal observational study in a large cohort of patients with primary membranous nephropathy and persistent nephrotic syndrome - Perna, Annalisa; Ruggiero, Barbara; Podestà, Manuel Alfredo; Perico, Luca; Orisio, Silvia; Debiec, Hanna; Remuzzi, Giuseppe; Ruggenenti, Piero (Frontiers in Pharmacology, 2022)
Rituximab is one of first-line therapies for patients with membranous nephropathy (MN) at high risk of progression towards kidney failure. We investigated whether response to Rituximab was affected by sex and antiPLA2R antibody levels in 204 consecutive patients (148 males and 56 females) with biopsy-proven MN who were referred to the Nephrology Unit of the Azienda Socio Sanitaria Territoriale Papa Giovanni XXIII from March 2001 to October 2016 and managed conservatively for at least six months. Primary outcome was a combined endpoint of complete (proteinuria <0.3 g/24h) or partial (proteinuria <3.0 g/24h and >50% reduction versus baseline) remission. Patients gave written informed consent to Rituximab treatment. The study was internally funded. No pharmaceutical company was involved. Anti PLA2R antibodies were detectable in 125 patients (61.3%). At multivariable analyses, female gender (p=0.0198) and lower serum creatinine levels (p=0.0108) emerged as independent predictors of better outcome (p=0.0198). The predictive value of proteinuria (p=0.054) and anti PLA2R titer (p=0.0766) was borderline significant. Over a median (IQR) of 24.8 (12.0-36.0) months, 40 females (71.4%) progressed to the combined endpoint as compared with 73 males (49.3%). Anti PLA2R titers at baseline [127.6 (35-7-310.8) vs 110.1 (39.9-226.7) RU/ml] and after Rituximab treatment were similar between sexes. However, the event rate was significantly higher in females than in males [HR (95%): 2.12 (1.44-3.12), p=0.0001]. Forty-five of the 62 patients (72.3%) with anti PLA2R titer below the median progressed to the combined end point versus 35 of the 63 (55.6%) with an higher titer [HR (95%): 1.97 (1.26-3.07), p<0.0029]. The highest probability to progress to the combined endpoint was observed in females with antiPLA2R antibody titer below median (86.7%), followed by females with antiPLA2R antibody titer above median (83.3%), males with titer below median (68.1%) and males with titer above median (44.4%). This trend was statistically significant (p=0.0023). Similar findings were observed for complete remission (proteinuria < 0.3 g/24h) and after analyses adjustments for baseline serum creatinine. Thus, despite similar immunological features, females were more resilient to renal injury following Rituximab therapy. These findings will hopefully open new avenues to identify the molecular pathways underlying sex-related nephroprotective effects.